PERAN MEDIASI PERBANKAN DALAM MENDORONG PERTUMBUHAN SEKTOR RIIL DI INDONESIA - Suryaningrum, Putu Eka; Sri Budhi, Made Kembar; Budiasa, Gede Sudjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.09.TAHUN 2016, 2016)
Monetary policy formulation has been organized by Bank of Indonesia in order to stabilize Indonesian economy as well as Bank Indonesia take function as monetary authorithy. This reaserach is found that the model as a whole have goodness of fits with R2 = 97%, therefor, only 3% of the prediction variation in dependent variable is influencing with other varables that is not included in the research model. This research is organized to aims the role of commercial banking credit as the significane factor in improving real sector growth in Indonesia, and instrument monetary policy of BI rate as well that would be combined with reserve requirenment called GWM. Those of policy combined are predicted as monetary policy stand for encouraging the real sector growth.
Keywords: transmision mecganism of credit and real sector performance